Prevalence and pattern of hearing loss among meningitis survivors in the Pacific Islands: a prospective, observational study protocol - Annette Kaspar; Sione Pifeleti; Carlie Driscoll (Journal of Global Health Reports)
# Background Permanent hearing loss is the most common neurological sequelae among meningitis survivors in low- and middle-income countries. It is preventable through the availability and optimal population coverage of immunization programs. The most recent Global Burden of Disease Project reported that mortality and morbidity rates associated with meningitis are in decline in the Pacific Islands. While the report is encouraging, clinical and rehabilitation services for meningitis survivors remain important for regions where immunization delivery is unable to reach optimal levels. The aim of the proposed study is to assess the prevalence and pattern of hearing impairment among meningitis survivors in Samoa, a Polynesian nation of the Pacific Islands.